Permasalahan pelajar-pelajar fakir miskin di daerah Sabak Bernam - Ab. Halim Tamuri; Zuria Mahmud; Safani Bari (penerbit ukm, 2005)
This study examined problems faced by students from poor families in the state of Selangor, especially in the district of Sabak Bernam. Forty-two students in Form 5 were selected as participants for this study. These group is made up of 19 students who stay in three community areas named Desa Kasih provided by the Pusat Zakat Selangor, and 23 who stayed outside of the community. Focus group interview was used to collect data. Results showed that students in this study exhibit healthy aspirations and positive values eventhough they faced financial constrains. The most obvious challenge for them in fulfilling their aspirations is their lifestyle, which is reflected by excessive TV watching, aimless conversations, and very little time allocated for revision, homework, or reading academic, spiritual, and general knowledge.